Societal Perception of Waste Water Management and Condition of Holy River Ganga in Varanasi City - Dwivedi, Amrita; Kumra, V.K. (National Geographical Journal of India, 2022)
This paper presents the current status of waste water management and related sanitation scenario in Varanasi city. The results are based on the personal survey conducted through questionnaire. It has been observed that the total sewage generated in the city is estimated to be 350 MLD, of which 102 MLD is treated at sewage treatment plants and the remaining discharged into the River Ganga and Varuna through open drains. The present condition of the river is alarming. In Varanasi alone, the Rever Ganga is being polluted everyday with over 250 MLD of untreated sewage. The sewer lines in the city are more than 80 years old and are prone to choking and leakages. Lack of suitable facilities (equipment and infrastructure) and under estimation of sewage waste generation rates, inadequate management and technical skills are the man problems before the administrators. Beside, there is real electrical power supply problem.As a result, the intermittent operation of sewage pumping stations and sewage treatment plants is ineffective in protecting water quality of the river Ganga and in provisioning safe drinking water and sanitation in Varanasi. People’s perception towards waste water management is found to be at variance, depending on their educational level, income and other constraints